2009
DOI: 10.1362/147539209x480963
|View full text |Cite
|
Sign up to set email alerts
|

Mass-customised products: are they bought for uniqueness or to overcome problems with standard products?

Abstract: Through mass customisation, firms can offer individualised products at little additional cost, which has prompted extensive research into the supply side but less investigation of consumer attitudes. Customers' willingness to pay more for mass-customised products may depend on their desire for unique products and use of such products in their self-presentations. It also may reflect their avoidance of the negative attributes of standardised, off-the-shelf products. These positive and negative motivations do not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Theory suggests that the consumers' general need for uniqueness (Tian et al 2001) or, more specifically, the consumers' desire for unique products (Lynn and Harris 1997) might impact the value toolkit users derive from the uniqueness of self-designed products (Fiore et al 2004;Michel et al 2006). Those consumers who specifically aim to differentiate themselves from others (i.e., who show a strong desire for unique products) should appreciate a truly unique product more (i.e., derive higher utility from the product) than consumers who aim for conformity (i.e., who show a low desire for unique products).…”
Section: Development Of Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Theory suggests that the consumers' general need for uniqueness (Tian et al 2001) or, more specifically, the consumers' desire for unique products (Lynn and Harris 1997) might impact the value toolkit users derive from the uniqueness of self-designed products (Fiore et al 2004;Michel et al 2006). Those consumers who specifically aim to differentiate themselves from others (i.e., who show a strong desire for unique products) should appreciate a truly unique product more (i.e., derive higher utility from the product) than consumers who aim for conformity (i.e., who show a low desire for unique products).…”
Section: Development Of Hypothesesmentioning
confidence: 99%
“…Fiore et al (2004) and Michel et al (2006) found that customers with a high general preference for unique products report significantly higher intentions to use MC systems. This suggests that the product uniqueness actually generated by an MC toolkit might contribute to the utility a consumer experiences.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The uniqueness of the product is the result of consumers who need uniqueness. A consumer's general need for uniqueness (Tian et al 2001) or, more specifically, a consumer's desire for a unique product (Lynn and Harris 1997) may have an impact on the value users derive from the uniqueness of a self-designed product (Fiore et al 2004;Michel et al 2006). Franke and Schreier (2008) explain that consumers who specifically aim to differentiate themselves from others (i.e., who show a strong desire for unique products) should value products that are truly unique (i.e., gain greater utility).…”
Section: The Effect Of Product Uniqueness On Consumer Satisfactionmentioning
confidence: 99%
“…In the present study, the desire for unique products is proposed at the situational level, since it can vary according to the situation or product itself (Michel et al, 2009) and the following hypothesis is proposed: H1. Desire for unique products has a positive direct effect on intention to purchase online mass-customised apparel products.…”
Section: Situational Traitsmentioning
confidence: 99%